Laser-scribed highly responsive infrared detectors with semi-reduced graphene oxide. (29th November 2017) - Feng, Rui; Zhang, Youwei; Hu, Laigui; Chen, Jing; Zaheer, Muhammad; Qiu, Zhi-Jun; Tian, Pengfei; Cong, Chunxiao; Nie, Qingmiao; Jin, Wei; Liu, Ran
Abstract: Graphene-based optoelectronic devices, including reduced graphene oxide (RGO) devices, commonly exhibit a large dark current and low on/off ratio with high dark-power consumption and a small responsivity. In this study, semi-RGO-based infrared photodetectors were directly "written" by using lasers, which can exhibit a small dark current of approximately 12 µA/cm 2 with a high responsivity of approximately 0.18 A/W at 1, 550 nm. Both the dark current and response speed can be tuned with GO as the gate dielectric in a field-effect transistor structure. These findings suggest the possibility of the three-dimensional "writing" of a micro-optoelectronic device or system with a low cost and high performance.